Use of satellite telemetry to evaluate movements of caribou within subsistence hunting areas in northern Alaska - Alexander K. Prichard; Geoffry M. Carroll; John C. George; Stephen M. Murphy; Mike D. Smith; Robert S. Suydam; David A. Yokel (Rangifer, 2003)
Caribou from the Teshekpuk Herd (TH) are an important subsistence resource for residents of Inupiaq villages in northern Alaska. In recent years the use of satellite telemetry has increased the understanding of the herd's annual movements and interactions with other herds. Most caribou of the TH are within the National Petroleum Reserve—Alaska (NPRA) throughout the year. The northeastern portion of NPRA has undergone two lease sales for oil and gas exploration, and lease sales are tentatively scheduled for the central/northwest portion of the NPRA in 2004. During 1990—1999, the movements of 27 caribou from the TH were tracked using satellite collars. We evaluated the proportion of time caribou were available to Inupiaq hunters by incorporating maps depicting subsistence-use areas for each of seven Inupiaq villages, and then examining seasonal and annual movements of caribou relative to those areas. By combining caribou locations with subsistence hunting areas, we were able to explore spatial and temporal patterns in caribou availability to subsistence hunters. This information is useful for managers to set appropriate hunting regulations and for devising sensible alternatives and mitigation of likely petroleum development in NPRA.